DAMPAK KESEJAHTERAAN GURU DI WILAYAH TERPENCIL DALAM MENANGANI KETIMPANGAN PENDIDIKAN - Ayu Lestari , Dina; Novianti, Yusda (Jurnal Berbasis Sosial, 2025)
Education Inequality In Remote Areas Is Still A Problem That Hinders The Equitable Distribution Of The Quality Of Education In Indonesia. One Of The Main Factors Is The Low Welfare Of Teachers Which Has A Direct Impact On Their Motivation And Performance. This Study Aims To Examine The Impact Of Teacher Welfare In An Effort To Overcome Educational Inequality In Remote Areas. The Method Used Is Qualitative With A Literature Study Approach, By Analyzing Various Literature And Previous Research Results. The Results Of The Study Show That The Welfare Of Teachers, Which Includes Economic Aspects, Facilities, And Social Support, Affects The Quality Of Learning. Improving Teachers' Welfare Is Able To Increase The Seriousness And Success Of Teaching, Which Ultimately Contributes To Reducing Educational Inequality. The Policy Of Improving Teacher Welfare Needs To Be A Priority In The Equitable Distribution Of National Education.